Settlement of an embankment treated with preloading and prefabricated vertical drain of east-coast highway phase 2 (a case study) - Nur Anis Adlina, Mat Noor (2012)
Soft soils are not suitable for construction of buildings or facilities without having soil improvements. The soil improvements that are used in the chosen site are Preloading and Prefabricated Vertical Drain (PVD). Analysis of settlement is important to evaluate the site before the construction begins. The objectives of the study are, to predict settlement of an embankment based on Terzaghi OneDimensional Consolidation analysis, to obtain the final settlement by using Asoaka's method based on monitoring data and to compare the soil properties from the lab data with back calculated based on the firn:il settlement. Using Terzaghi One-Dimensional Consolidation Method, prediction of the total settlement is 287mm. The data from monitoring record are used to plot Asoaka's Graph in order to get the actual settlement which is 13mm, then being used to back calculate soil properties. The soil properties those are back calculated based on field settlement are different from those obtained from lab data. The differences can be seen by the correlation between the field and lab, which are for the Coefficient of Vertical Consolidation, Cv field = 0.04 Cv lab, the correlation for Coefficient of Horizontal Consolidation, ch field = 0.04 ch lab, the correlation for the Compression Index, Cc field = 0.043 Cc lab and the correlation of Recompression Index, Cr field = 0.06 Cr lab. This particular correlation can be used as a design guideline to similar site condition.